2D nanoporous Ni(OH)2 film as an electrode material for high-performance energy storage devices. Issue 31 (5th June 2019) - Tian, Jinjun; Xue, Yan; Yu, Xinping; Pei, Yuanchao; Zhang, Hucheng; Wang, Jianji
Abstract : A two-dimensional (2D) nanoporous Ni(OH)2 film was successfully developed from triethanolamine (TEA) as the alkali source and soft template using a scalable hydrothermal technique. Abstract : A two-dimensional (2D) nanoporous Ni(OH)2 film was successfully developed from triethanolamine (TEA) as the alkali source and soft template using a scalable hydrothermal technique. The nanostructured Ni(OH)2 film was flexible and translucent, and could be directly compressed on a current collector. Owing to the uniform well-defined morphology and stable structure, the Ni(OH)2 film binder-free electrode displayed a high specific capacity, exceptional rate capability, and admirable cycle life. The specific capacitance was 453.6 mA h g −1 (1633 F g −1 ) at 0.5 A g −1 . The assembled Ni(OH)2 //activated carbon (AC) asymmetric supercapacitor (ASC) device had an energy density of 58.7 W h kg −1 at a power density of 400 W kg −1 . These prominent electrochemical properties of Ni(OH)2 were attributed to the high electrical conductivity, high surface area, and unique porous architecture. Free tailoring, binder-free, and direct pressing were the most significant achievements of the Ni(OH)2 film in the development of high-performance energy storage devices.